Acute Reciprocal Changes Distant from the Site of Spinal Osteotomies Affect Global Postoperative Alignment. (4th October 2011) - Klineberg, Eric; Schwab, Frank; Ames, Christopher; Hostin, Richard; Bess, Shay; Smith, Justin S.; Gupta, Munish C.; Boachie, Oheneba; Hart, Robert A.; Akbarnia, Behrooz A.; Burton, Douglas C.; Lafage, Virginie
Abstract : Introduction . Three-column vertebral resections are frequently applied to correct sagittal malalignment; their effects on distant unfused levels need to be understood. Methods . 134 consecutive adult PSO patients were included (29 thoracic, 105 lumbar). Radiographic analysis included pre- and postoperative regional curvatures and pelvic parameters, with paired independent t -tests to evaluate changes. Results . A thoracic osteotomy with limited fusion leads to a correction of the kyphosis and to a spontaneous decrease of the unfused lumbar lordosis (−8°). When the fusion was extended, the lumbar lordosis increased (+8°). A lumbar osteotomy with limited fusion leads to a correction of the lumbar lordosis and to a spontaneous increase of the unfused thoracic kyphosis (+13°). When the fusion was extended, the thoracic kyphosis increased by 6°. Conclusion . Data from this study suggest that lumbar and thoracic resection leads to reciprocal changes in unfused segments and requires consideration beyond focal corrections.